Bi-modal stimulation in the treatment of tinnitus: a study protocol for an exploratory trial to optimise stimulation parameters and patient subtyping. Issue 10 (25th October 2017) - D'Arcy, Shona; Hamilton, Caroline; Hughes, Stephen; Hall, Deborah A; Vanneste, Sven; Langguth, Berthold; Conlon, Brendan
Abstract : Introduction: Tinnitus is the perception of sound in the absence of a corresponding external acoustic stimulus. Bimodal neuromodulation is emerging as a promising treatment for this condition. The main objectives of this study are to investigate the relevance of interstimulus timing and the choices of acoustic and tongue stimuli for a proprietary bimodal (auditory and somatosensory) neuromodulation device, as well as to explore whether specific subtypes of patients are differentially responsive to this novel intervention for reducing the symptoms of chronic tinnitus. Methods and analysis: This is a two-site, randomised, triple-blind, exploratory study of a proprietary neuromodulation device with a pre–post and 12-month follow-up design. Three different bimodal stimulation parameter sets will be examined. The study will enrol 342 patients, split 80:20 between two sites (Dublin, Ireland and Regensburg, Germany), to complete 12 weeks of treatment with the device. Patients will be allocated to one of three arms using a stepwise stratification according to four binary categories: tinnitus tonality, sound level tolerance (using loudness discomfort level of <60 dB SL as an indicator for hyperacusis), hearing thresholds and presence of a noise-induced audiometric profile. The main indicators of relative clinical efficacy for the three different parameter sets are two patient-reported outcomes measures, the Tinnitus Handicap Inventory and the Tinnitus Functional Index, after 12 weeks of intervention. Clinical efficacy will be further explored in a series of patient subtypes, split by the stratification variables and by presence of a somatic tinnitus. Evidence for sustained effects on the psychological and functional impact of tinnitus will be followed up for 12 months. Safety data will be collected and reported. A number of feasibility measures to inform future trial design include: reasons for exclusion, completeness of data collection, attrition rates, patient's adherence to the device usage as per manufacturer's instructions and evaluation of alternative methods for estimating tinnitus impact and tinnitus loudness. Ethics and dissemination: This study protocol is approved by the Tallaght Hospital/St. James's Hospital Joint Research Ethics Committee in Dublin, Ireland, and by the Ethics Committee of the University Clinic Regensburg, Germany. Findings will be disseminated to relevant research, clinical, health service and patient communities through publications in peer-reviewed and popular science journals and presentations at scientific and clinical conferences. Trial registration number: The trial is registered on ClinicalTrials.gov (NCT02669069 ) Pre-results.